(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2023)
The digital economy has ushered in a new era of business and innovation, reshaping industries and challenging traditional economic models. Central to this transformation is the concept of value creation, which plays a unique and pivotal role in the digital age. In this thesis, we will explore how value creation takes on distinct characteristics and importance in the digital economy.